Digitalizing Culture in Education: A Local Wisdom-Based E-Book on Balinese Songs for Fourth Graders - Kristina, Ni Kadek Sindy Dwi; Sujana, I Wayan; Suniasih, Ni Wayan (Mimbar Ilmu, 2024)
This study was motivated by the inability of educators or teachers to provide engaging and innovative learning media. This issue significantly impacts students' learning outcomes, which remain low or below the Minimum Competency Criteria (KKM). Therefore, it is essential to develop a learning medium that addresses students' learning challenges. The aim of this research is to develop a local wisdom-based electronic book (E-Book) focusing on Balinese songs with the theme "My Region and Its Natural Resources" in the teaching of Natural and Social Sciences (IPAS) for fourth-grade elementary school students. This study employs the ADDIE development model with 16 fourth-grade elementary school students as research subjects. The findings indicate that the E-Book's design assessment achieved a score of 90.91%, categorized as excellent. The E-Book's feasibility was confirmed through expert evaluations, with a learning content expert scoring 90.63%, an instructional design expert scoring 91.25%, and a media expert scoring 90.91%, all categorized as excellent. In individual trials, the E-Book scored 94.64%, and in small group trials, it scored 93.25%, both of which are categorized as excellent. Furthermore, the effectiveness test yielded a calculated tvalue of 7.097. Based on these results, it can be concluded that the local wisdom-based E-Book on Balinese songs with the theme "My Region and Its Natural Resources" is effective for use in the IPAS learning process for fourth-grade elementary school students.